2015
DOI: 10.1002/ijc.29614
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel radiochemotherapy approaches targeting prostate tumor progenitor cells using nanohybrids

Abstract: Many tumors including prostate cancer are maintained by cancer stem cells (CSCs), which might cause tumor relapse if not eradicated during the course of treatment. Specific targeting or radiosensitization of CSCs bear promise to improve tumor curability by synergistic effects in combination with radiotherapy. Carbon nanotubes (CNTs) can be used as promising drug delivery systems for anticancer drugs such as the flavonoid catechin. Catechin is an extensively studied active ingredient of the different plants, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Functional nanohybrids Table 6 have also been prepared by developing covalent bonds between the polyphenol and the polymer through a radical reaction. In this regard, catechin–gelatin conjugate [ 137 , 138 ] and quercetin–methacrylic acid conjugate [ 139 , 140 ] were used as the coating material for multi-walled carbon nanotubes. The obtained nanotherapeutics were found to have enhanced anticancer activity in HeLa cancer cells, compared with the free flavonoids [ 137 , 139 ].…”
Section: Polyphenol-loaded Polymeric Nanotherapeutics For Cancer Tmentioning
confidence: 99%
“…Functional nanohybrids Table 6 have also been prepared by developing covalent bonds between the polyphenol and the polymer through a radical reaction. In this regard, catechin–gelatin conjugate [ 137 , 138 ] and quercetin–methacrylic acid conjugate [ 139 , 140 ] were used as the coating material for multi-walled carbon nanotubes. The obtained nanotherapeutics were found to have enhanced anticancer activity in HeLa cancer cells, compared with the free flavonoids [ 137 , 139 ].…”
Section: Polyphenol-loaded Polymeric Nanotherapeutics For Cancer Tmentioning
confidence: 99%
“…Regarding PCa and BC applications utilizing carbon-based NPs there is an increasing number of publications during the last couple of years, both for imaging and therapy but also for different kind of electrochemical biosensor systems [226,227,228,229,230,231,232,233,234]. For instance, regarding PCa, Heydari-Bafrooei et al and Pan et al have both developed different kind of CNT-based biosensor systems able to detect prostate specific antigen (PSA) in serum and vascular endothelial growth factor (VEGF) and PSA in serum, respectively, for early diagnosis of PCa [227,229].…”
Section: Nanoparticles For Prostate and Breast Cancermentioning
confidence: 99%
“…Catechin is in the family of polyphenolic flavonoids, and catechin and its derivatives (2)-epigallocatechin-3-gallate, (2)-epigallocatechin, (2)-epicatechin-3-gallate, and (2)-epicatechin inhibit cancer cell proliferation, suppress tumor growth and metastasis, and sensitize tumors to various chemotherapy drugs and radiotherapy [ 44 45 46 ]. Recently, a study showed that biocompatible catechin-loaded and gelatin-conjugated carbon nanotubes have good anticancer properties with the potential for targeting prostate PCa stem cells in combination with x-ray irradiation [ 47 ].…”
Section: Nanomedicine Delivery For Prostate Cancermentioning
confidence: 99%